ChemInform Abstract: From One‐Photon to Two‐Photon Probes: "Caged" Compounds, Actuators, and Photoswitches. Issue 33 (25th July 2013) - Bort, Guillaume; Gallavardin, Thibault; Ogden, David; Dalko, Peter I.
Abstract Review: 127 refs.